2020
DOI: 10.5387/fms.2019-17
|View full text |Cite
|
Sign up to set email alerts
|

Higher modified Glasgow Prognostic Score and multiple stapler firings for rectal transection are risk factors for anastomotic leakage after low anterior resection in rectal cancer

Abstract: Objective : Anastomotic leakage (AL) is one of the most devastating complications of rectal cancer surgery. Not only does AL result in reduced quality of life, extended hospitalization and impaired defecatory function, it also has a high local recurrence rate. In this study, we investigated risk factors for AL as it may help to decrease its occurrence and improve patient outcomes. Methods : This study was a retrospective, singleinstitution study of rectal cancer patients who underwent elective low anterior res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Several recent studies have reported the utility of various in ammation-based and/or nutritional markers as predictors of postoperative complications and poor prognosis in esophageal cancer, such as the Onodera's prognostic nutritional index (PNI), CRP-to-albumin ratio (CAR) and modi ed Glasgow prognostic score (mGPS), which are calculated based on laboratory data including serum albumin or CRP [6][7][8]. Some studies have reported preoperative PNI, CAR and mGPS as predictors for AL after gastrointestinal cancer surgery [9][10][11]. However, no studies appear to have examined the association between preoperative in ammationbased and/or nutritional markers and AL after esophageal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported the utility of various in ammation-based and/or nutritional markers as predictors of postoperative complications and poor prognosis in esophageal cancer, such as the Onodera's prognostic nutritional index (PNI), CRP-to-albumin ratio (CAR) and modi ed Glasgow prognostic score (mGPS), which are calculated based on laboratory data including serum albumin or CRP [6][7][8]. Some studies have reported preoperative PNI, CAR and mGPS as predictors for AL after gastrointestinal cancer surgery [9][10][11]. However, no studies appear to have examined the association between preoperative in ammationbased and/or nutritional markers and AL after esophageal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported the utility of various inflammation-based and/or nutritional markers as predictors of postoperative complications and poor prognosis in esophageal cancer, such as the Onodera’s prognostic nutritional index (PNI), CRP-to-albumin ratio (CAR) and modified Glasgow prognostic score (mGPS), which are calculated based on laboratory data including serum albumin or CRP [ 6 8 ]. Some studies have reported preoperative PNI, CAR and mGPS as predictors for AL after gastrointestinal cancer surgery [ 9 11 ]. However, no studies appear to have examined the association between preoperative inflammation-based and/or nutritional markers and AL after esophageal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Three or more cartridges of the linear stapler are a risk factor for anastomotic leakage. [23][24][25] In addition, recent systematic evaluation has shown that using two cartridges also have a higher incidence of anastomotic leakage than using one during laparoscopic rectal cancer resection. 26 In all of our patients with anastomotic leaks, the number of stapler cartridges used was more than two, which may have contributed to a higher incidence of anastomotic leaks in the conventional surgery group.…”
Section: Discussionmentioning
confidence: 99%